2021
DOI: 10.1371/journal.pntd.0009513
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic characteristics associated with dengue fever in 2011–2016 in Bang Phae district, Ratchaburi province, Thailand

Abstract: Background Dengue is a major public health problem in Thailand, but data are often focused on certain dengue-endemic areas. Methods: To better understand dengue epidemiology and clinical characteristics in Thailand, a fever surveillance study was conducted among patients aged 1–55 years, who presented with non-localized febrile illness at Bang Phae Community Hospital in Ratchaburi province, Thailand from October 2011 to September 2016. Results Among 951 febrile episodes, 130 were dengue-confirmed. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…These subjects who sought care also reported that they had a previous dengue infection over the interval, but this was not verified with information on medical charts. In the same catchment population in Bangphae district during an overlapping study period, there was a facility-based fever surveillance study [ 21 ]. These serosurvey subjects who sought care for febrile illness at BPCH during the interval between serosurvey visits were enrolled in our fever surveillance study and tested for acute dengue fever (with IgM/IgG ELISA and RT-PCR) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These subjects who sought care also reported that they had a previous dengue infection over the interval, but this was not verified with information on medical charts. In the same catchment population in Bangphae district during an overlapping study period, there was a facility-based fever surveillance study [ 21 ]. These serosurvey subjects who sought care for febrile illness at BPCH during the interval between serosurvey visits were enrolled in our fever surveillance study and tested for acute dengue fever (with IgM/IgG ELISA and RT-PCR) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the same catchment population in Bangphae district during an overlapping study period, there was a facility-based fever surveillance study [ 21 ]. These serosurvey subjects who sought care for febrile illness at BPCH during the interval between serosurvey visits were enrolled in our fever surveillance study and tested for acute dengue fever (with IgM/IgG ELISA and RT-PCR) [ 21 ]. There were few of these serosurvey subjects who were captured in the surveillance ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…albopictus , and widely used and highly safe vaccines and antiviral treatments currently exist [ 2 ]. In addition to interventions targeting the disease via the vector, such as insecticide application, clinical management can also be used to intervene in the spread of the disease [ 4 ]. However, existing strategies have proven insufficient for dealing with the significant increase in cases of dengue fever reported worldwide [ 5 ].…”
Section: Introductionmentioning
confidence: 99%